Course of Hyperkalemia in Patients on Hemodialysis. (28th April 2022) - Spinowitz, Bruce; Fishbane, Steven; Fukagawa, Masafumi; Ford, Martin; Guzman, Nicolas; Rastogi, Anjay
Abstract : Background . Evidence of longitudinal serum potassium (sK + ) concentrations in hyperkalemic hemodialysis patients is sparse. Objective . These post hoc analyses of the placebo arm of the phase 3b DIALIZE study (NCT03303521) explored the course of hyperkalemia in hemodialysis patients receiving placebo. Methods . In DIALIZE, 196 patients receiving hemodialysis three times weekly were randomized to placebo or sodium zirconium cyclosilicate 5 g starting dose once daily on nondialysis days for 8 weeks. In these post hoc analyses of placebo patients overall ( n = 86) and by predialysis sK + subgroups at randomization <5.5 mmol/L, 5.5 to <6.0 mmol/L, 6.0 to <6.5 mmol/L, and ≥6.5 mmol/L, we assessed mean predialysis sK + concentration by visit and the proportions of patients with mean predialysis sK + ranges of 4.0–5.0 and 4.0–5.5 mmol/L by visit. Results . In placebo patients, the mean predialysis sK + concentration at randomization was 5.9 mmol/L, and 5.8 mmol/L at the end of the study (day 57). For placebo patients overall and across all predialysis sK + subgroups, the mean predialysis sK + concentration remained ≥5.0 mmol/L for all visits over 8 weeks. Overall, 7–21% and 27–62% of placebo patients had predialysis sK + ranges of 4.0–5.0 and 4.0–5.5 mmol/L, respectively, at any visit. The proportions of placebo patients with either predialysis sK + range were greatest for those who were least hyperkalemic (<5.5 mmol/L) and generally decreased with increasing predialysis sK + concentration. Conclusions . Patients receiving placebo and hemodialysis maintained high predialysis sK + concentrations over 8 weeks following a hyperkalemic event. Most placebo patients remained hyperkalemic and may be at continued risk of adverse events.